Implications Of The Time Value Of Money Concept On Sharia-Based Retirement Planning Based On Dsn-Mui Fatwa No. 88/Dsn-Mui/X/2013 - Anwar Syarif; Muhammad Yafiz (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Implementing the time value of money in pension funds cannot be separated from the knowledge of economists, the need for literature related to this matter, especially about the time value of money, where the value of money today will not be the same as the value of money in the future, MUI Fatwa No. 88/DSN-MUI/X/2013 provides guidelines for sharia-based pension fund management, prioritizing the principles of justice, transparency and halal investment. This research reviews the implications of the TVM concept in the context of sharia-based retirement planning in accordance with the guidelines of MUI Fatwa No. 88/DSN-MUI/X/2013. The research method used is library research using various secondary sources as research material. This type of research uses library research where the author combines and collects data by reading articles and books to produce accurate data. The research results found that the application of sharia principles in managing pension funds can provide a guarantee of fair and sustainable value for pension participants. This research highlights the importance of synergy between TVM principles and sharia guidelines in retirement planning.